Acid-decorated chitosan-magnetic aluminum ferrite as a bionanocomposite catalyst for green synthesis of biologically active [4,3‑d]pyrido[1,2‑a]pyrimidin-6‑ones - Maryam Saberi-Zare; Mohammad Ali Bodaghifard (Scientific Reports)
Abstract In this study, a novel hybrid nanostructure consisting of acid-decorated chitosan and magnetic AlFeO3 nanoparticles was fabricated. The acid-decorated chitosan provided a stable and biocompatible matrix for the magnetic AlFeO3 nanoparticles. Various techniques including Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction patterns (XRD), thermogravimetric analysis (TGA), vibrating sample magnetometry (VSM), specific surface area (BET), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS) were used to characterize and confirm the successful synthesis of the hybrid nanostructure. The newly prepared magnetic bio-nanocomposite (AlFeO3@CS-SO3H) was effectively employed in the synthesis of biologically active 7-aryl[4,3d]pyrido[1,2a]pyrimidin-6(7H)one derivatives in an aqueous medium, creating an environmentally friendly process. The desired products were manufactured in high yields (88–98%) without the formation of noticeable side products. This procedure offers numerous advantages, including short reaction times, the use of a green solvent, the ability to reuse the catalyst without a significant decrease in catalytic activity, and easy separation of the catalyst using an external magnet. The high yields and minimal side product formation indicate the efficiency and selectivity of this method, making it a promising strategy for the sustainable production of biologically active compounds.